2020
DOI: 10.2147/ott.s261700
|View full text |Cite
|
Sign up to set email alerts
|

<p>Paclitaxel Suppresses Hepatocellular Carcinoma Tumorigenesis Through Regulating Circ-BIRC6/miR-877-5p/<em>YWHAZ</em> Axis</p>

Abstract: Background: Paclitaxel is an effective chemotherapeutic agent for the treatment of cancer patients. Accumulating evidence suggests that circular RNAs (circRNAs) play critical roles in the occurrence and development of human cancers. However, there are few studies on interactions between paclitaxel and circRNAs in hepatocellular carcinoma (HCC). Materials and Methods: Cell counting kit-8 (CCK-8) assay and colony formation assay were conducted to determine cell proliferation. Cell apoptosis was assessed by flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…YWHAZ has been shown to be commonly upregulated in multiple cancers, especially HCC, as it can promote tumorigenesis, metastasis, and chemoresistance in the progression of cancer[ 19 - 21 ]. Our bioinformatic analysis showed that RAF1 was strongly coexpressed with YWHAZ (Figure 3E ).…”
Section: Discussionmentioning
confidence: 99%
“…YWHAZ has been shown to be commonly upregulated in multiple cancers, especially HCC, as it can promote tumorigenesis, metastasis, and chemoresistance in the progression of cancer[ 19 - 21 ]. Our bioinformatic analysis showed that RAF1 was strongly coexpressed with YWHAZ (Figure 3E ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence showed that increased LOX could promote angiogenesis, induce epithelial-mesenchymal transition, and is related to early recurrence of HCC ( Umezaki et al, 2019 ; Yang et al, 2019 ). Furthermore, accumulated evidence has demonstrated that multiple molecules mediated the tumorigenesis and metastasis of HCC by regulating the YWHAZ -associated axis ( Zhao et al, 2018 ; Wei et al, 2019 ; Liu et al, 2020a ; Shen et al, 2020 ). Bioinformatic analysis also revealed the miR-139-5p/ CCT5 axis might exert a momentous effect on HCC progression, but in-depth validated studies have not been carried out ( Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Circ_PVT1 repressed gastric cancer resistance to PTX via binding to miR-124-3p [ 28 ]. Circ_BIRC6 overexpression relieved PTX-induced repression of hepatocellular carcinoma progression through trapping miR-877-5p [ 29 ]. Additionally, circ_ZFR promoted PTX resistance in lung cancer in a miR-195-5p-dependent manner [ 30 ].…”
Section: Discussionmentioning
confidence: 99%